Dinamika Politik Perempuan dalam Kontestasi Pilkada di Provinsi Lampung - Salim, Choirul (Tapis: Jurnal Penelitian Ilmiah, 2019)
The involvement of women in politics in Indonesia, especially in the contestation of the Local Election (pilkada) has become an interesting conversation lately. On June 27, 2018, the democratic party elections for regional heads simultaneously in Lampung Province were quite satisfactory for women's leadership, which certainly gave a little hope in the midst of the lack of representation of women in Lampung's political arena. This field research that explains the political dynamics of women in the regional election contestation in Lampung from the perspective of obstacles and women's political strategies in the elections in Lampung. Based on the results of the study it can be concluded that the political dynamics of women in the Lampung elections are very closely related to the influence of figures, political communication and the mass base they have. Women who enter politics can defeat various stereotypes about women even though there are societies that give choices in the elections because of monetary rewards. Women's political strategy in the elections is to show the community that women are not inferior to men and convince the public with various programs that will be fought for when they get a position.